Le chat est-il (encore) un média interactif? - Guillaume LATZKO-TOTH (Tic & Société)
This paper traces the emergence of online chat as a communication device (through analyzing the genenis of main artifacts) and strives to deconstruct the obviousness of its status of interactive media. It does so by first suggesting “strong” (normative) hypotheses on what makes a media “interactive”, then by showing that this form of computer-mediated communication (CMC) has been articulated in two different ways. One is rather convivial and sociability-oriented – chat “rooms” – while the other is more instrumental and focused on efficiency – instant messaging systems. The soaring of the latter at the expense of “convivial” chat spaces appears as a turn in the social construction of this practice, reflecting the rise of networked individualism, and inviting us to reassess the interactivity of online chat as a “social media”.